MATURE GONADAL BROODSTOCK SELECTION IN GONGGONG CONCH Laevistrombus turturella (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Gonggong conch Laevistrombus turturella is a sea conch that has been consumed by many people in Kepulauan Riau Province so the population is expected to decline. One of the efforts to conserve conchs is through culture. Culture activities require the availability of the mature gonad broodstock. The aim of this study was to analyze the size of a mature gonadal of gonggong conch based on the shell length and the color of gonads, and to evaluate the effect of different temperature exposures in the speed of determining the sexual of broodstock. The conch shell length was measured by a caliper, then were broken to observe the gonad color. Data were analyzed by student t-test. The exposure treatments with water temperatures of 15°C (P1), 20°C (P2) and 30°C (P3). Seven conch broodstocks were put into the aquarium according to the treatment, the duration of time the soft gonggong conch body came out of the shell was recorded. Data were analyzed with the Kruskal Wallis test. The results showed that the average length of the mature gonad gonggong conch broodstocks from Madong-Tanjungpinang sea were 63.449±5.352 mm (males) and 66.953±5.876 mm (females). Determination of the gonggong conch broodstock sexual can be accelerated with thermal shock on water temperature of 20°C